An approach to the study of financial consumption in the low-income sectors of Buenos Aires, Argentina - Hadad, Iara Nadina (2017)
An approach is proposed on the study of financial consumption in the low-income sectors of Argentina. As mentioned in multiple research studies conducted in different Latin American countries, the study of this recent and widespread phenomenon demands to highlight some of the common places that have caused the characterization of the economic life of the popular sectors. We propose some theoretical guidelines to reconsider such consumption and analyze the results of our still ongoing investigation regarding consumption and indebtedness in the lower sectors of the metropolitan area of Buenos Aires.